Characterization of the Cr-C/Si3N4 Composite Coatings Electroplated from a Trivalent Chromium Bath. (10th August 2016) - Liao, Chia-Wen; Lee, Hung-Bin; Hou, Kung-Hsu; Jian, Shun-Yi; Lu, Chen-En; Ger, Ming-Der
Graphical abstract: SEM micrograph (BSE mode) showing the surface of (a) Cr-C coating and (b) Cr-C-Si3 N4 composite coating containing Si3 N4 of 17.22 vol%. Highlights: The Cr-C-Si3 N4 composite coatings are prepared by electrochemical deposition. The Si3 N4 particles had great influence on structure and properties of coatings. Cr-C-Si3 N4 composite coating has better mechanical performances than Cr-C coating. The Si3 N4 particles can greatly increase the hardness of composite coating. The wear resistance is significantly improved by adding Si3 N4 particles. Abstract: Cr-C/Si3 N4 composite coatings are obtained by electrodeposition under DC conditions from a trivalent chromium plating bath containing suspended Si3 N4 nanoparticles. The influences of plating parameters including Si3 N4 concentration in the plating bath and current density on the coating composition, deposition rate, morphology, surface roughness, micro-hardness and wear behavior of electrodeposited Cr-C/Si3 N4 composite coatings are evaluated and compared with that of electrodeposited Cr-C coating. Our study reveals that Si3 N4 particles can be successfully codeposited and uniformed distributed in the electrodeposited Cr-C matrix. The maximum level of incorporation of Si3 N4 particles, about 17.22 vol%, is obtained at a bath loading of 5 g L −1 and at a current density of 20 A dm −2 . Due to enhanced dispersion strengthening effect, the incorporation of Si3 N4 particles increases the microhardness of the coatings and significantly increases the wear resistance of the coatings.